O26 Development and piloting of a regional simulation programme for foundation doctors. (5th November 2017) - Gilmore, A; Whitcombe, A; White, G; Hellaby, M
Abstract : Background: It has been recognised that there is significant variability in access to simulation-based learning for foundation doctors across the North West of England, with some organisations not providing any. In a bid to remove this inequality a simulation-based programme for foundation doctors was developed to encourage employing hospital trusts to increase their activity. The proposed course was piloted at a representative acute teaching hospital site. Methodology: A triangulated learning needs analysis was undertaken. This included a literature review, a survey sent to all North West foundation year doctors asking them to suggest useful scenarios and aggregated clinical incident data involving foundation doctors in the UK for the last ten years. The identified content was then mapped to the Foundation Programme curriculum and resources developed for a program of four sessions, two sessions for each year. Resources included scenarios, simulated patient briefings and diagnostics including blood tests and ECGs. Sessions were preferentially delivered utilising simulated patients rather than a manikin unless this was impractical such as in a defibrillation scenario. Scenarios were peer reviewed and evidence based on a regional template and preceded a debriefing based on a learning discussion. Pilot sessions were evaluated through a combination of pre- and post-learning questionnaires using validated metrics that looked at participant satisfaction, self-assessed confidence, change in knowledge and attitudes. Results: Eight sessions were facilitated at the pilot site for a total of twenty foundation doctors who all attended both sessions. All participants agreed they had learnt from the sessions. Whilst the sample size was relatively small it was still possible to demonstrate a statistically significant increase of knowledge in certain areas. The underpinning knowledge in some of the areas was recognised as poor and it was felt that some pre-learning would have assisted in maximising learning opportunities. Additionally because of the topics involved such pre-learning could be made available for more novice faculty. Conclusions: The pilot was well received and seemed an achievable programme that could significantly reduce the burden on local trusts looking to develop a foundation simulation programme. It is hoped that this will improve equity of access to simulation based learning opportunities and promote patient safety across the North West of England.